1989
DOI: 10.1111/j.1600-0536.1989.tb04754.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐application occlusion substantially increases the irritant response of the skin to repeated short‐term sodium lauryl sulfate (SLS) exposure

Abstract: Occlusion often, but not always, enhances percutaneous absorption and thus may facilitate skin irritation. Quantitative data about the impact occlusivity may have on minimal irritant stimuli to which the skin is exposed in daily life, and which may lead to chronic irritant contact dermatitis, are however lacking. Irritant stimuli were administered by repeated application of sodium lauryl sulfate (SLS) in an open application procedure. After the open exposure, the skin was either left open or occluded with plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…Additionally, occlusion may increase the irritation potential of the topically administered API. For instance, Van der Valk and Maibach have shown that in ten healthy subjects the irritation response to repeated short-term exposure of sodium lauryl sulfate was enhanced with postexposure occlusion [95]. Functional damage to the skin barrier by occlusion, detected by transepidermal water loss, has also been reported [96].…”
Section: Challenges and Solutions For Overcoming Skin Irritationmentioning
confidence: 99%
“…Additionally, occlusion may increase the irritation potential of the topically administered API. For instance, Van der Valk and Maibach have shown that in ten healthy subjects the irritation response to repeated short-term exposure of sodium lauryl sulfate was enhanced with postexposure occlusion [95]. Functional damage to the skin barrier by occlusion, detected by transepidermal water loss, has also been reported [96].…”
Section: Challenges and Solutions For Overcoming Skin Irritationmentioning
confidence: 99%
“…Soap with a low pH (5·7) induced erythema and pruritus which did not occur at higher pH (9·5) (29). In another study, on the effects of occlusion, it was found that postexposure occlusion by a plastic wrap caused more severe irritation compared with unoccluded exposures to SLS (21). The degree of augmentation of the irritant response by occlusion differs between varying types of substances.…”
Section: Extrinsic Factors That Determine the Outcome Of Human Skin Imentioning
confidence: 99%
“…In turn, these protective measures may produce negative events due to the nature of occlusion, which often causes stratum corneum hyper-hydration and reduces the protective barrier properties of the skin (12). Many gloves do not resist the penetration of low molecular weight chemicals: those chemicals may enter the glove and become trapped on the skin under occlusion for many hours, possibly leading to irritation, and more seriously, to dermatitis or eczematous changes (13)(14)(15). Wound dressings have been employed to speed the healing processes in acute and chronic wounds by keeping healing tissues moist and increasing superficial wound epithelialization (2,16,17).…”
mentioning
confidence: 99%